Public Support for “Get Smart” Criminal Justice Reform Post-2020: Virginia as a Case Study - Mancini, Christina (International journal of offender therapy and comparative criminology, 2023)
Over the last decade, some states have considered reforms to address the consequences of “get tough” justice. The passage of recreational marijuana laws—albeit incorporated across a minority of jurisdictions—is just one popular example. While recent scholarship indicates support for such measures among the public, there is a need for exploration of public views in light of the social unrest of 2020. Additionally, there is a need to understand public views across jurisdictions that are diverse. Accordingly, Virginia stands out as an ideal case study as it is the first state in the South to incorporate or consider a variety of progressive justice reforms. Drawing on a statewide poll conducted in 2021 (N = 1,017), this study explores the extent to which Virginians support recreational marijuana legislation, the repeal of mandatory minimums, and a moratorium on the death penalty. Findings indicate that approval varies by measure and that there are divides in public views, specifically, across socio-demographic dimensions (e.g., political ideology), and also across views about the state of society and willingness to fund the justice system. Implications are discussed.